Figurative Language Used in King Lier Novel by Willian Shakespeare: Explorer Literary Appreciation - Saputra, Frian; Kurniawati, Ari; Yuniarti, Vyna; Hayati, Sri (CV. Doki Course and Training, 2024)
This study explores the use of figurative language in William Shakespeare's